Synergity of religion, culture and arts: meeting point model of religious education for ustadz, culturals and artists in Garut district - Syahidin Syahidin; Muhamad Parhan; Risris Hari Nugraha (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2023)
Garut Regency is a religious area with good Human Resources (HR) potential, including many religious instructors, religious teachers, cultural figures, and artists. They became community figures who were influential enough to move the wheels of development in Garut society with a spiritual, arts, and cultural approach. However, their current existence has not been able to motivate people to improve their quality of life. The root of the problem is misperceptions among community leaders, especially religious counselors, religious teachers, artists, and cultural figures. They view that religious education or Islamic da'wah and the development of arts and culture are two different things and even tend to be contradictory. A qualitative research approach using descriptive analysis methods from field studies by synergizing and discussing with religious, arts, and cultural figures, then conducting workshops, preparing and disseminating model drafts in the form of limited training as a trial of the cultural approach to religious education model for religious instructors, Ustadz, Artists and Cultural People in Garut Regency. This activity aims to equalize perceptions about Islam and arts and culture and to create good synergy between religion, arts, and culture. This community service produces new ideas and models of religious education with an arts and culture approach that elevates and socializes local wisdom.   Abstrak Kabupaten Garut dikenal sebagai daerah religius dan memiliki potensi Sumber Daya Manusia (SDM), yang cukup baik, di antaranya banyak penyuluh agama, ustadz, budayawan dan para seniman. Mereka menjadi tokoh masyarakat yang cukup berpengaruh untuk menggerakan roda pembangunan di masyarakat Garut dengan pendekatan agama dan seni budaya. Namun keberadaan mereka saat ini belum mampu memotivasi masyarakat untuk meningkatkan kualitas hidup mereka. Akar persoalannya adalah karena adanya kesalahan persepsi di kalangan tokoh masyarakat, khususnya para penyuluh keagamaan, para ustadz, seniman, dan budayawan. Mereka memandang bahwa pendidikan keagamaan atau dakwah Islam dengan pengembangan seni budaya merupakan dua hal yang berbeda bahkan cenderung kontradiktif. Pendekatan penelitian secara kualitatif dengan metode deskriptif analisis dari studi lapangan dengan melakukan sinergi dan berdiskusi dengan tokoh agama, seni dan budaya, kemudian melakukan workshop, penyusunan dan sosialisasi draf model dalam bentuk Pelatihan terbatas sebagai uji coba Model pendidikan keagamaan pendekatan budaya bagi para penyuluh keagamaan, ustadz, seniman, dan budayawan di Kabupaten Garut. Kegiatan ini bertujuan untuk menyamakan persepsi tentang Islam dan seni budaya serta terjadi sinergitas yang baik di antara agama, seni dan budaya. Pengabdian kepada Masyarakat ini menghasilkan gagasan-gagasan baru dan model-model pendidikan keagamaan dengan pendekatan seni budaya yang mengangkat dan mensosialisasikan kearifan lokal. Kata Kunci: Budayawan; kearifan lokal; model pembinaan keagamaan; penyuluh agama; seniman; ustadz